BIOASSAY OF BIOORGANIC FERTILIZER OF PAPER MILL SLUDGE TO IMPROVE GROWTH AND NUTRIENT STATUS OF CORN - Happy Widiastuti; Siswanto ,; Suharyanto , (JURNAL SELULOSA, 2012)
The study was aimed to test the effectiveness of organic sludge fertilizer on growth, nutrient status of plants and metal content of maize seed produced. Experiments was conducted to test 7 treatments namely without fertilizer (A), 100% of inorganic fertilizer (B), fertilized with bioorganic granule fertilizer formula 4 + 50% inorganic fertilizer (C), fertilized with bulk bioorganic sludge fertilizer formula 4 + 50% inorganic fertilizer (D), fertilized with granule formula 16 + 50% inorganic fertilizer (E), fertilized with bulk bioorganic formula 16 + 50% inorganic fertilizer (F), fertilized with bulk bioorganic sludge fertilizer 4 + humic acid +50% inorganic fertilizer (G) arranged in randomized completely block design with 5 replications. Bioorganic sludge fertilizer formula 4 contains Azotobacter sp. while formula 16 containing consortium of phosphate solubilizing bacteria + Azotobacter sp. + Trichoderma sp. Addition of bioorganicsludge fertilizer in combination with 50% mineral fertilizer resulted similar growth of corn compared to those of 100% mineral fertilizer. The addition of granule bioorganic sludge fertilizer formula 4 resulted significantly higher N and P nutrient status of corn plants both in terms of leaves, stems, roots, and seeds. Metal content of Mo, Co, B and Pb was higher in maize seed treated with bioorganic sludge fertilizer (G16) compared to mineral fertilizer. However, 100% mineral fertilizer yield maize seed containing Cu, Zn, Mn, and Fe higher than those of fertilized with sludge bioorganic fertilizer.Keywords: bioorganic sludge fertilizer, corn, nutrient uptake, metal uptake  ABSTRAK Penelitian bertujuan menguji keefektifan pupuk bioorganik sludge (PBS) terhadap pertumbuhan, status hara tanaman dan kandungan logam biji jagung yang dihasilkan. Percobaan dilakukan untuk menguji tujuh perlakuan pupuk yaitu tanpa pupuk (A), pupuk anorganik 100% (B), PBS granul formula 4 + pupuk anorganik 50% (C), PBS curah formula 4 + pupuk anorganik 50% (D), PBS granul formula 16 + pupuk anorganik 50% (E), PBS curah formula 16 + pupuk anorganik 50% (F), PBS curah formula 4 + asam humat + pupuk anorganik 50% (G) yang disusun dalam rancangan lengkap acak kelompok dengan lima ulangan. Pupuk formula 4 mengandung Azotobacter sp. sedangkan formula 16 mengandung konsorsium bakteri pelarut fosfat, Azotobacter sp., dan Trichoderma sp. Penambahan PBS yang dikombinasi dengan pupuk anorganik 50% menghasilkan pertumbuhan yang sama dengan jagung yang diberi pupuk anorganik 100%. Pemberian PBS granul formula 4 menghasilkan status hara N dan P jaringan tanaman nyata lebih tinggi dibandingkan dengan yang dipupuk anorganik. Kandungan logam Mo, Co, B dan Pb lebih tinggi dalam biji jagung yang diberi PBS (G16) dibandingkan dengan yang dipupuk anorganik dan kontrol. Pemberian pupuk anorganik 100% menghasilkan biji jagung yang mengandung Cu, Zn, Mn, dan Fe lebih tinggi daripada yang diberi PBS.Kata kunci: pupuk bioorganik sludge, jagung, serapan hara, serapan logam